Kepastian Hukum Surat Kuasa Mutlak dalam Hal Tanah sebagai Objek Hak Tanggungan - Wiramansyah, Fahrel Faadhilah; Saputra, Alfian Anugrah; Maulana, Hasbi Ilman; Murtadha, Afif Nafis (Universitas Ekasakti, 2023)
Absolute power in the case of land objects was initially prohibited in accordance with the provisions of the Minister of Home Affairs Instruction Number 14 of 1982 concerning the Prohibition of the Use of Absolute Power of Attorney as a Transfer of Land Rights and Government Regulation Number 24 of 1997 concerning Land Registration. The use of absolute power can then be permitted in accordance with the provisions of the Letter of the Director General of Agrarian Affairs on behalf of the Minister of Home Affairs of the Republic of Indonesia Number 594/493/AGR dated 31 March 1982 and the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 10 of 2014 concerning the Revocation of Legislation Regarding Land. The purpose of this research is to explore the limits of absolute power that can or cannot be used in the case of land as an object of mortgage rights as an embodiment of legal certainty by referring toestablished rightwhile exploring the legal consequences. The type of legal research used is normative. The approach used in this research is statutory, conceptual and case regulations. The results of the research found that the limits of absolute power that can be used are inseparable from the main agreement which includes that all rights attached to the parties have been fulfilled. The grant of power cannot then be substituted. The legal consequences are attached to the agreement, namely that it can be canceled or null and void by law. Legal certainty regarding the use of absolute power has not yet been realized, because there are no explicit statutory regulations that regulate absolute power.